Challenges in Implementing Nursing Theory-based Practice in Clinical Care: A Mixed-Method Study - Joyce Joseph; Suganya Panneerselvam; Vaishali Raipuriya (Journal of Nature and Science of Medicine, 2025)
Aim: This study aimed to explore the barriers to implementing Nursing Theory-based Practices in the clinical setting among nursing personnel working at a tertiary care center in India. Methods: A convergent parallel mixed-method study was conducted using a simple random sampling (quantitative phase) of 325 nursing personnel and a nonprobability convenient sampling (qualitative phase) of 6 nursing personnel at a tertiary care center in East-central India. A self-structured tool was used to assess the barriers among nursing personnel through Google form and an in-depth interview was conducted among nursing personnel. Data were analyzed separately for both phases and in the interpretation phase, it was mixed. Results: A total of 325 nurses were interviewed in this study. The quantitative analysis shows majority had a medium barrier level in knowledge and implementation 282 (86.6%), personal interest 217 (66.8%) and role of institutions 235 (72%). The qualitative analysis shows nurses believed that nursing theories are insufficient in teaching and difficult to learn and apply the process, which makes them unfamiliar and less important. The lack of training on theory application from the student period itself has reduced their interest in theories. There was a lack of autonomy in providing care and a lack of support in the workplace to practice their nursing theories. Conclusions: Practicing nursing theories in the clinical setting will promote better patient care. Nursing theories and their utilization contribute to the richness of the nursing profession and provide an identity to the profession, so there is a need for managerial support, skilled nurses, and the conduction of educational activities to foster the culture of nursing theory-based nursing care.